2005
DOI: 10.3748/wjg.v11.i7.964
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of Tie-1 and Tie-2 receptors, and angiopoietins-1, 2 and 4 in colorectal adenocarcinoma:Immunohistochemical analysis and correlation with clinicopathological factors

Abstract: These findings suggest that the Tie-Ang receptor-ligand complex is one of the factors involved in the cellular differentiation and progression of human colorectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Angiopoietin family members usually regulate the differentiation or invasion of cancer cells through the activation of its receptor Tie-2 and downstream tyrosine kinase pathway (8,9,41). However, ANGPTL4 does not bind to Tie-2 but contains motifs structurally conserved in angiopoietins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiopoietin family members usually regulate the differentiation or invasion of cancer cells through the activation of its receptor Tie-2 and downstream tyrosine kinase pathway (8,9,41). However, ANGPTL4 does not bind to Tie-2 but contains motifs structurally conserved in angiopoietins.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the angiopoietin family is involved in the regulation of tumour progression, cellular growth and differentiation (8)(9)(10). Angiopoietin-like 4 (ANGPTL4) is a member of the family of angiopoietins and is known as hepatic fibrinogen/angiopoietin-related protein (HEARP) (11), peroxisome proliferator-activated receptor-Á (PPARÁ) angiopoietin-related gene (PGAR) (12) or fastinginduced adipose factor (FIAF) (13).…”
Section: Introductionmentioning
confidence: 99%
“…there is strong evidence that the angiopoietin family is involved in the regulation of tumour progression, cellular growth, and differentiation (4)(5)(6). Angiopoietin-like 4 (Angptl4) is a member of the family of angiopoietins and is also known as hepatic fibrinogen/angiopoietin-related protein (HeArp) (7), peroxisome proliferator-activated receptor-γ (ppArγ) angiopoietin-related gene (pgAr) (8), or fasting-induced adipose factor (FIAF) (9).…”
Section: Introductionmentioning
confidence: 99%
“…The coexpression of Ang-1, -2 and -4 and Tie-1 and -2 has been reported in tumor cells, suggesting the presence of an autocrine and/or a paracrine angiopoietin/Tie growth pathway in solid tumors [35][36][37][38] . Angiopoietins (Angs) also have been shown to play a role in the proliferation and/or differentiation of stromal tumors and normal mesenchymal cells [41,42] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that Ang-1 and Ang-4 can activate Tie-1 [33] . Coexpression of angiopoietin and its receptor, either Tie-1 or Tie-2, has been reported in tumor cells, suggesting the presence of an autocrine and/or a paracrine angiopoietin/Tie growth pathway in solid tumors [34][35][36] . Further, the expression levels of angiopoietin and its receptors have been shown to correlate with progressive tumor growth and development of metastasis by many types of carcinomas [35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%